Halogen-free flame-retardant epoxy resin copper-clad plate and preparation method thereof

By using nitrogen-containing expanded flame retardant and modified aluminum hydroxide in copper clad plates, combined with mesoporous silica modification technology, the toxicity and performance problems of traditional flame retardant are solved, and the copper clad plate with halogen-free flame retardant and high impact resistance is achieved.

CN119795697AActive Publication Date: 2025-04-11JIANG SU YAO HONG ELECTRONICS CO LTD

Patent Information

Application Number
CN202510012545.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The halogen-based flame retardants used in existing copper clad plates will produce toxic substances when burned, and inorganic flame retardants need to be added in large quantities to achieve good results, which affects the overall performance of copper clad plates, and the phosphorus-containing flame retardants will put pressure on the environment.

Method used

A swelling flame retardant containing nitrogen was used and vinyl mesoporous silica was prepared by cocondensation, and polyvinyl alcohol modified mesoporous silica was prepared by alcoholylation reaction. The composite flame retardant was combined with modified aluminum hydroxide to improve the flame retardant and impact resistance of the copper clad plate.

Benefits of technology

Halogen-free flame-retardant copper clad plate is achieved, which improves its long-term stability and flame-retardant properties, while enhancing impact resistance, avoiding the toxicity and environmental pollution problems of traditional flame retardants.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of copper-clad plates, and particularly discloses a halogen-free flame-retardant epoxy resin copper-clad plate and a preparation method thereof. According to the copper-clad plate, an intumescent flame retardant is loaded on mesoporous silica to prepare a composite flame retardant, and the composite flame retardant and modified aluminum hydroxide are mixed for use. The preparation method has the beneficial effects that the intumescent flame retardant is loaded on mesoporous silica, a foam carbon layer structure formed after combustion can isolate air and heat conduction, a polymer main body is protected, and the purpose of flame retardance is achieved; meanwhile, modified aluminum hydroxide is introduced, and the aluminum hydroxide has good flame retardance and can promote generation of a carbon layer in the combustion process; on the other hand, silicon dioxide and aluminum hydroxide serve as inorganic filler, the mechanical property of the copper-clad plate can be improved, and the problem that the impact resistance is reduced due to introduction of the intumescent flame retardant is solved; meanwhile, the mesoporous carbon dioxide loaded flame retardant can fix the intumescent flame retardant in the resin, so that the mobility of the intumescent flame retardant is reduced, and the flame retardant property of the copper-clad plate is not reduced after long-term storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper clad laminates, in particular to a halogen-free flame-retardant epoxy resin copper clad laminate and a preparation method thereof. Background Art

[0002] Copper clad laminate, also known as copper clad laminate (CCL), is a plate-like material made by impregnating glass fiber cloth with resin, covering one or both sides with copper foil and hot pressing. It is the core substrate of printed circuit boards (PCB). Epoxy resin refers to a class of polymer compounds containing two or more epoxy groups in the molecular structure. Epoxy resin has the advantages of good chemical resistance, dimensional stability, low price, and high bonding strength, so it is widely used in CCL. However, epoxy resin is flammable and releases a large amount of toxic gas when burned. Therefore, flame retardants are added to improve its performance in CCL production. At present, the most commonly used flame retardants on the market are halogen-based flame retardants, but they will produce toxic substances when burned, posing a great safety hazard; in addition, inorganic flame retardants can also be used, but in order to achieve good results, a large amount of inorganic materials need to be added, which will affect the overall performance of CCL; another method is to introduce phosphorus-containing flame retardants into the resin material. Although good results can be achieved, as the scale of electronic product use continues to expand, phosphorus-containing electronic waste will cause great pressure on the environment over time.

[0003] In summary, it is of great significance to solve the above problems and manufacture a halogen-free flame-retardant epoxy resin copper clad laminate. Summary of the invention

[0004] The object of the present invention is to provide a halogen-free flame-retardant epoxy resin copper clad laminate and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a halogen-free flame-retardant epoxy resin copper-clad laminate, comprising the following steps:

[0006] S1: Preparation of vinyl mesoporous silica by co-condensation of silane mixed precursors under acidic conditions;

[0007] S2: obtaining polyvinyl acetate-modified mesoporous silica by copolymerization, and then preparing polyvinyl alcohol-modified mesoporous silica by alcoholysis reaction;

[0008] S3: (1) using polyvinyl alcohol modified mesoporous silica as a carbon source, mixing it with an acid source and a gas source, and connecting them through aldehyde as a reaction reagent to prepare a composite flame retardant; (2) treating aluminum hydroxide with a silane coupling agent to obtain modified aluminum hydroxide;

[0009] S4: bisphenol A epoxy resin, curing agent, curing accelerator, solvent, composite flame retardant and modified aluminum hydroxide are mixed and stirred to obtain a prepreg, the glass fiber cloth is immersed in the prepreg for 5 to 20 minutes, and cured at 60 to 90° C. for 10 to 30 minutes to obtain a prepreg;

[0010] S5: After laminating one or more layers of the semi-cured sheet, both sides are covered with copper foil, pressed at 5-30 MPa and 120-200° C. for 3-6 hours, and kept warm for 1-3 hours to obtain a halogen-free flame-retardant epoxy resin copper-clad laminate.

[0011] Among them, the specific process of S1 is: dissolving poly (ethylene glycol)-block-poly (propylene glycol)-block-poly (ethylene glycol) in a hydrochloric acid solution, adding tetraethoxysilane while stirring, reacting for 1 to 3 hours, adding vinyl triethoxysilane while stirring, reacting for 1 to 3 hours, heating to 60 to 100 ° C, standing for 18 to 24 hours, filtering and then extracting with ethanol Soxhlet for 18 to 24 hours, and finally drying at 60 to 100 ° C for 8 to 16 hours to obtain vinyl mesoporous silica;

[0012] Preferably, the raw material components of the vinyl mesoporous silica are as follows: 50-80 parts of poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol), 90-120 parts of tetraethoxysilane, 80-100 parts of vinyltriethoxysilane, 200-300 parts of hydrochloric acid, and 3000-4000 parts of deionized water;

[0013] Among them, the specific process of S2 is: vinyl mesoporous silica, vinyl acetate, azobisisobutyronitrile and methanol are mixed evenly, stirred at 50-80°C for reaction, when the reactant becomes viscous, an appropriate amount of methanol is added to dilute it, and after cooling, the product is dried and crushed to obtain polyvinyl acetate modified mesoporous silica; polyvinyl acetate modified mesoporous silica, sodium hydroxide and methanol are mixed evenly, continuously stirred at 30-60°C, filtered after the reaction is completed, and dried to obtain polyvinyl alcohol modified mesoporous silica;

[0014] Preferably, the raw material components of the polyvinyl acetate modified mesoporous silica are as follows: 30-80 parts of vinyl mesoporous silica, 100-300 parts of vinyl acetate, 0.1-1 parts of azobisisobutyronitrile, and 60-90 parts of methanol;

[0015] Preferably, the raw materials of the polyvinyl alcohol-modified mesoporous silica are as follows: 20 to 50 parts of polyvinyl acetate-modified mesoporous silica, 2 to 6 parts of sodium hydroxide, and 100 to 150 parts of methanol;

[0016] Among them, in S3, the preparation process of the composite flame retardant is: the acid source, the gas source, and the aldehyde are mixed evenly, the temperature is raised to 40-60° C., and the mixture is continuously stirred. After reacting for 1-3 hours, polyvinyl alcohol-modified mesoporous silica is added, and the mixture is continuously stirred at 40-60° C. and reacted for 12-24 hours to obtain the composite flame retardant;

[0017] Preferably, the raw material components of the composite flame retardant are as follows: 1-3 parts of polyvinyl alcohol-modified mesoporous silica, 3-8 parts of acid source, 1-3 parts of gas source, and 0.1-2 parts of aldehyde;

[0018] Preferably, the acid source includes but is not limited to one of amino-containing sulfhydryls and amino-containing benzene sulfonates; the gas source includes but is not limited to one of melamine and melamine derivatives;

[0019] More preferably, the acid source is sodium p-aminobenzenesulfonate; the gas source is melamine;

[0020] Wherein, in S3, the modified aluminum hydroxide preparation process is: adding aluminum hydroxide, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and anhydrous ethanol into a ball mill, and taking out after ball milling for 1 to 5 hours without drying to obtain modified aluminum hydroxide;

[0021] Preferably, the weight proportions of the raw materials of the modified aluminum hydroxide are: 10 to 30 parts of aluminum hydroxide, 1 to 5 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and 1 to 5 parts of anhydrous ethanol;

[0022] The raw materials of the prepreg are as follows: 80-120 parts of bisphenol A epoxy resin, 5-15 parts of curing agent, 2-8 parts of curing accelerator, 40-80 parts of solvent, 20-50 parts of composite flame retardant, and 5-20 parts of modified aluminum hydroxide.

[0023] Preferably, the curing agent includes but is not limited to one of dicyandiamide and phenolic resin; the curing accelerator includes but is not limited to one of imidazoles and tertiary amines; the solvent includes but is not limited to one of acetone, dimethylformamide, ethylene glycol methyl ether and toluene.

[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0025] The present invention adopts nitrogen-containing intumescent flame retardant to replace traditional flame retardant, and adopts polyhydroxy polyvinyl alcohol as carbon source, which can be quickly dehydrated by dehydrating agent to form carbon layer when burning; sodium p-aminobenzenesulfonate is used as acid source, which can decompose to produce acid when burning, and then esterify with carbon source to dehydrate it; melamine will release non-toxic gas after heating, so that the carbon layer has good foam structure, which can isolate air and heat conduction, protect polymer body, and achieve flame retardant purpose. However, the compatibility of intumescent flame retardant with resin is poor, and it is easy to affect the impact resistance of copper clad laminate after use. On the other hand, intumescent flame retardant is easy to seep out in resin system, which affects the stability of copper clad laminate in long-term storage.

[0026] Mesoporous silica can be used as an adsorption material due to its unique hexagonal structure. By synthesizing vinyl mesoporous silica and then copolymerizing and alcoholyzing it with vinyl acetate, polyvinyl alcohol-modified mesoporous silica can be obtained. Then, aldehyde is used as a reaction reagent to connect it with an acid source and a gas source, which can fix the intumescent flame retardant on the mesoporous silica and restrict its flow, which can improve the long-term stability of the copper clad laminate. On the other hand, as a commonly used filler for copper clad laminates, silica can improve the thermal stability, mechanical properties and dielectric properties of copper clad laminates.

[0027] In addition, the composite flame retardant and modified aluminum hydroxide can improve the overall flame retardancy of the copper clad laminate on the one hand; on the other hand, an appropriate amount of aluminum hydroxide can also improve the overall impact resistance of the copper clad laminate to a certain extent. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The following examples include the following raw materials: hydrochloric acid (CAS No. 7647-01-0), poly (ethylene glycol)-block-poly (propylene glycol)-block-poly (ethylene glycol) (Pluronic P123) (CAS No. 9003-11-6), tetraethoxysilane (CAS No. 78-10-4), vinyl triethoxysilane (CAS No. 78-08-0), vinyl acetate (CAS No. 108-05-4), azobisisobutyronitrile (CAS No. 78-67-1), methanol (CAS No. 67-56-1), sodium hydroxide (CAS No. 1310-73-2), sodium p-aminobenzenesulfonate (CAS No. 15898-43-8), melamine (CAS No. 108-78-1), formaldehyde (CAS No. : 50-00-0), aluminum hydroxide (CAS No.: 21645-51-2), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (CAS No.: 2530-83-8), anhydrous ethanol (CAS No.: 64-17-5), bisphenol A type epoxy resin (CAS No.: 25085-99-8), dicyandiamide (CAS No.: 461-58-5), 2-ethyl-4-methylimidazole (CAS No.: 931-36-2), acetone (CAS No.: 67-64-1), silicon dioxide (CAS No.: 7631-86-9).

[0030] Example 1: S1: 250 parts of hydrochloric acid were dissolved in 4000 parts of deionized water to obtain a hydrochloric acid solution, 65 parts of Pluronic P123 were dissolved in the hydrochloric acid solution, 105 parts of tetraethoxysilane were added while stirring, and after reacting for 2 hours, 95 parts of vinyltriethoxysilane were added while stirring, and after reacting for 2 hours, the temperature was raised to 80°C, and the mixture was allowed to stand for 24 hours. After filtering, the mixture was extracted with ethanol Soxhlet for 24 hours, and finally dried at 80°C for 12 hours to obtain vinyl mesoporous silica;

[0031] S2: 50 parts of vinyl mesoporous silica, 180 parts of vinyl acetate, 0.5 parts of azobisisobutyronitrile and 80 parts of methanol were mixed evenly, and stirred at 65°C for reaction. When the reactant became viscous, an appropriate amount of methanol was added to dilute it. After cooling, the product was dried and crushed to obtain polyvinyl acetate modified mesoporous silica; 30 parts of polyvinyl acetate modified mesoporous silica, 4 parts of sodium hydroxide and 100 parts of methanol were mixed evenly, and stirred continuously at 45°C. After the reaction was completed, the mixture was filtered and dried to obtain polyvinyl alcohol modified mesoporous silica;

[0032] S3: (1) Mix 4 parts of sodium p-aminobenzenesulfonate, 2 parts of melamine and 1 part of formaldehyde, heat to 50°C, stir continuously, react for 2 hours, then add 2 parts of polyvinyl alcohol-modified mesoporous silica, stir continuously at 50°C, react for 24 hours, and obtain a composite flame retardant; (2) Add 20 parts of aluminum hydroxide, 1 part of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 1 part of anhydrous ethanol into a ball mill, mill for 3 hours, take out without drying, and obtain modified aluminum hydroxide;

[0033] S4: 100 parts of bisphenol A epoxy resin are heated to 50° C., 10 parts of dicyandiamide, 5 parts of 2-ethyl-4-methylimidazole, 60 parts of acetone, 50 parts of composite flame retardant, and 5 parts of modified aluminum hydroxide are added, and stirred for 5 minutes to obtain a prepreg; the glass fiber cloth is immersed in the prepreg for 15 minutes, and cured at 80° C. for 15 minutes to obtain a semi-cured sheet;

[0034] S5: The front and back sides of the single-layer prepreg are covered with copper foil, and hot pressed in a press at 15 MPa and 200° C. for 4 hours, and kept warm for 2 hours to obtain a halogen-free flame-retardant epoxy resin copper-clad laminate.

[0035] Example 2: S1: 250 parts of hydrochloric acid were dissolved in 4000 parts of deionized water to obtain a hydrochloric acid solution, 65 parts of Pluronic P123 were dissolved in the hydrochloric acid solution, 105 parts of tetraethoxysilane were added while stirring, and after reacting for 2 hours, 95 parts of vinyltriethoxysilane were added while stirring, and after reacting for 2 hours, the temperature was raised to 80°C, and the mixture was allowed to stand for 24 hours. After filtering, the mixture was extracted with ethanol Soxhlet for 24 hours, and finally dried at 80°C for 12 hours to obtain vinyl mesoporous silica;

[0036] S2: 50 parts of vinyl mesoporous silica, 180 parts of vinyl acetate, 0.5 parts of azobisisobutyronitrile and 80 parts of methanol were mixed evenly, and stirred at 65°C for reaction. When the reactant became viscous, an appropriate amount of methanol was added to dilute it. After cooling, the product was dried and crushed to obtain polyvinyl acetate modified mesoporous silica; 30 parts of polyvinyl acetate modified mesoporous silica, 4 parts of sodium hydroxide and 100 parts of methanol were mixed evenly, and stirred continuously at 45°C. After the reaction was completed, the mixture was filtered and dried to obtain polyvinyl alcohol modified mesoporous silica;

[0037] S3: (1) Mix 5 parts of sodium p-aminobenzenesulfonate, 3 parts of melamine and 1.2 parts of formaldehyde, heat to 50°C, stir continuously, react for 2 hours, then add 3 parts of polyvinyl alcohol-modified mesoporous silica, stir continuously at 50°C, react for 24 hours, and obtain a composite flame retardant; (2) Add 20 parts of aluminum hydroxide, 1 part of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 1 part of anhydrous ethanol into a ball mill, mill for 3 hours, take out without drying, and obtain modified aluminum hydroxide;

[0038] S4: 120 parts of bisphenol A epoxy resin are heated to 50° C., 12 parts of dicyandiamide, 6 parts of 2-ethyl-4-methylimidazole, 65 parts of dimethylformamide, 30 parts of composite flame retardant, and 15 parts of modified aluminum hydroxide are added, and stirred for 5 minutes to obtain a prepreg; the glass fiber cloth is immersed in the prepreg for 15 minutes, and cured at 80° C. for 15 minutes to obtain a semi-cured sheet;

[0039] S5: The three layers of prepreg are stacked and covered with copper foil on both sides, and hot pressed at 15 MPa and 200° C. for 4 hours in a press, and kept warm for 2 hours to obtain a halogen-free flame-retardant epoxy resin copper-clad laminate.

[0040] Example 3: S1: 250 parts of hydrochloric acid were dissolved in 4000 parts of deionized water to obtain a hydrochloric acid solution, 65 parts of Pluronic P123 were dissolved in the hydrochloric acid solution, 105 parts of tetraethoxysilane were added while stirring, and after reacting for 2 hours, 95 parts of vinyltriethoxysilane were added while stirring, and after reacting for 2 hours, the temperature was raised to 80°C, and the mixture was allowed to stand for 24 hours. After filtering, the mixture was extracted with ethanol Soxhlet for 24 hours, and finally dried at 80°C for 12 hours to obtain vinyl mesoporous silica;

[0041] S2: 50 parts of vinyl mesoporous silica, 180 parts of vinyl acetate, 0.5 parts of azobisisobutyronitrile and 80 parts of methanol were mixed evenly, and stirred at 65°C for reaction. When the reactant became viscous, an appropriate amount of methanol was added to dilute it. After cooling, the product was dried and crushed to obtain polyvinyl acetate modified mesoporous silica; 30 parts of polyvinyl acetate modified mesoporous silica, 4 parts of sodium hydroxide and 100 parts of methanol were mixed evenly, and stirred continuously at 45°C. After the reaction was completed, the mixture was filtered and dried to obtain polyvinyl alcohol modified mesoporous silica;

[0042] S3: (1) Mix 3 parts of sodium p-aminobenzenesulfonate, 3 parts of melamine and 1.5 parts of formaldehyde, heat to 50°C, stir continuously, react for 2 hours, then add 3 parts of polyvinyl alcohol-modified mesoporous silica, stir continuously at 50°C, react for 24 hours, and obtain a composite flame retardant; (2) Add 20 parts of aluminum hydroxide, 1 part of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 1 part of anhydrous ethanol into a ball mill, mill for 3 hours, take out without drying, and obtain modified aluminum hydroxide;

[0043] S4: 100 parts of bisphenol A epoxy resin are heated to 50° C., 10 parts of dicyandiamide, 5 parts of 2-ethyl-4-methylimidazole, 60 parts of acetone, 20 parts of composite flame retardant, and 20 parts of modified aluminum hydroxide are added, and stirred for 5 minutes to obtain a prepreg; the glass fiber cloth is immersed in the prepreg for 15 minutes, and cured at 80° C. for 15 minutes to obtain a semi-cured sheet;

[0044] S5: After the five layers of prepreg are stacked, they are covered with copper foil on both sides, and hot pressed in a press at 15 MPa and 200° C. for 4 hours, and kept warm for 2 hours to obtain a halogen-free flame-retardant epoxy resin copper-clad laminate.

[0045] Comparative Example 1: Taking Example 1 as a control, the modified aluminum hydroxide was removed in Comparative Example 1, and the other processes remained unchanged.

[0046] Comparative Example 2: S1: (1) 4 parts of sodium p-aminobenzenesulfonate, 2 parts of melamine and 1 part of formaldehyde were mixed evenly, heated to 50°C, stirred continuously, reacted for 2 hours, and then 2 parts of polyvinyl alcohol were added. Stirring continuously at 50°C, reacted for 24 hours, and an intumescent flame retardant was obtained; (2) 20 parts of aluminum hydroxide, 20 parts of silicon dioxide, 2 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 2 parts of anhydrous ethanol were added to a ball mill, ball milled for 3 hours, and then taken out without drying to obtain a modified inorganic filler;

[0047] S2: 100 parts of bisphenol A epoxy resin were heated to 50°C, 10 parts of dicyandiamide, 5 parts of 2-ethyl-4-methylimidazole, 60 parts of acetone, 50 parts of intumescent flame retardant, and 15 parts of modified inorganic filler were added, and stirred for 5 minutes to obtain a prepreg; the glass fiber cloth was immersed in the prepreg for 15 minutes, and cured at 80°C for 15 minutes to obtain a semi-cured sheet;

[0048] S3: The front and back sides of the single-layer prepreg are covered with copper foil, and hot pressed in a press at 15 MPa and 200° C. for 4 hours, and kept warm for 2 hours to obtain a halogen-free flame-retardant epoxy resin copper-clad laminate.

[0049] Comparative Example 3: S1: Deionized water was heated to 70°C, and then 20 parts of polyvinyl alcohol was added while stirring, and the temperature was maintained at 70-90°C until the polyvinyl alcohol was completely dissolved, and 50 parts of mesoporous silica was added to the solution, and the mixture was stirred at 70°C for 3h, filtered and freeze-dried to obtain polyvinyl alcohol-modified mesoporous silica;

[0050] S2: (1) Mix 4 parts of sodium p-aminobenzenesulfonate, 2 parts of melamine and 1 part of formaldehyde, heat to 50°C, stir continuously, react for 2 hours, then add 2 parts of polyvinyl alcohol-modified mesoporous silica, stir continuously at 50°C, react for 24 hours, and obtain a composite flame retardant; (2) Add 20 parts of aluminum hydroxide, 1 part of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 1 part of anhydrous ethanol into a ball mill, mill for 3 hours, take out, and obtain modified aluminum hydroxide without drying;

[0051] S3: 100 parts of bisphenol A epoxy resin are heated to 50° C., 10 parts of dicyandiamide, 5 parts of 2-ethyl-4-methylimidazole, 60 parts of acetone, 50 parts of composite flame retardant, and 5 parts of modified aluminum hydroxide are added, and stirred for 5 minutes to obtain a prepreg; the glass fiber cloth is immersed in the prepreg for 15 minutes, and cured at 80° C. for 15 minutes to obtain a semi-cured sheet;

[0052] S4: The front and back sides of the single-layer prepreg are covered with copper foil, and hot pressed in a press at 15 MPa and 200° C. for 4 hours, and kept warm for 2 hours to obtain a halogen-free flame-retardant epoxy resin copper-clad laminate.

[0053] Test experiment 1: The prepregs prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were cut into samples of 80×10×2.5 mm, and their impact resistance was tested according to standard ASTM D256-2010; their limiting oxygen index was tested according to standard ASTM D2863-2008, and the data are shown in Table 1.

[0054] <![CDATA[Impact strength / (KJ / m 2 )]]> Oxygen index / % Example 1 6.41 34.4 Example 2 6.39 33.8 Example 3 6.43 33.7 Comparative Example 1 5.87 29.4 Comparative Example 2 6.19 31.5 Comparative Example 3 6.37 32.8

[0055] Table 1

[0056] Test experiment 2: The semi-cured sheets prepared in Example 1 and Comparative Examples 2 and 3 were stored in a dry environment away from direct sunlight for 12 months. After being taken out, the surface was observed to see if it was wet. The limiting oxygen index test data were tested according to standard ASTM D2863-2008 as shown in Table 2.

[0057] Is the surface wet? Oxygen index / % Oxygen index drop rate Example 1 no 34.1 0.87% Comparative Example 2 yes 23.8 24.4% Comparative Example 3 yes 27.3 16.8%

[0058] Table 2

[0059] Conclusion: By comparing the results of Examples 1 to 3, it can be seen that as the mass fraction of the composite flame retardant decreases, the mass fraction of the modified aluminum hydroxide increases, the oxygen index gradually decreases, and the flame retardancy gradually decreases, but the difference in impact strength performance is small, so Example 1 has the best performance. By comparing Example 1 with Comparative Example 1, it can be found that the impact performance of the composite flame retardant alone cannot be guaranteed, and its flame retardancy is not as good as that of the modified aluminum hydroxide flame retardant. This is because aluminum hydroxide has the effect of promoting carbonization and can serve as a synergist of the intumescent flame retardant. From the data analysis of Example 1 and Comparative Example 2 in Tables 1 and 2, it can be seen that it is feasible to directly add the intumescent flame retardant to the resin and ensure its flame retardancy and mechanical properties by adding inorganic fillers in the short term. However, as the storage time becomes longer, the intumescent flame retardant not loaded by mesoporous silica in Comparative Example 3 has seepage, and at this time, the performance gap in flame retardancy is large compared with that of the product in Example 1; from the results analysis of Example 1 and Comparative Example 3, it can be seen that the composite flame retardant prepared by directly using polyvinyl alcohol to modify mesoporous silica has a large gap in flame retardant effect after long-term storage compared with Example 1. This is because the present invention first copolymerizes mesoporous silica and vinyl acetate, introduces polyvinyl acetate on the surface of mesoporous silica, and then obtains polyvinyl alcohol-modified mesoporous silica by alcoholysis. Polyvinyl alcohol and mesoporous silica are connected by chemical bonds, while in Comparative Example 3, polyvinyl alcohol and mesoporous silica are directly mixed and freeze-dried, and the two are only connected by hydrogen bonds. Therefore, Example 1 can better reduce the mobility of the composite flame retardant and ensure its stable performance after long-term storage.

[0060] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a halogen-free flame-retardant epoxy resin copper-clad laminate, characterized in that: The following steps are involved: S1: Preparation of vinyl mesoporous silica by co-condensation of silane mixed precursors under acidic conditions; S2: obtaining polyvinyl acetate-modified mesoporous silica by copolymerization, and then preparing polyvinyl alcohol-modified mesoporous silica by alcoholysis reaction; S3: (1) using polyvinyl alcohol modified mesoporous silica as a carbon source, mixing it with an acid source and a gas source, and connecting them through aldehyde as a reaction reagent to prepare a composite flame retardant; (2) treating aluminum hydroxide with a silane coupling agent to obtain modified aluminum hydroxide; S4: bisphenol A epoxy resin, curing agent, curing accelerator, solvent, composite flame retardant and modified aluminum hydroxide are mixed and stirred to obtain a prepreg, the glass fiber cloth is immersed in the prepreg for 5 to 20 minutes, and cured at 60 to 90° C. for 10 to 30 minutes to obtain a prepreg; S5: After laminating one or more layers of the semi-cured sheet, both sides are covered with copper foil, pressed at 5-30 MPa and 120-200° C. for 3-6 hours, and kept warm for 1-3 hours to obtain a halogen-free flame-retardant epoxy resin copper-clad laminate.

2. The method for preparing a halogen-free flame-retardant epoxy resin copper-clad laminate according to claim 1, characterized in that: The specific process of S1 is: dissolving poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) in a hydrochloric acid solution, adding tetraethoxysilane while stirring, reacting for 1 to 3 hours, adding vinyltriethoxysilane while stirring, reacting for 1 to 3 hours, heating to 60 to 100°C, standing for 18 to 24 hours, filtering and then extracting with ethanol Soxhlet for 18 to 24 hours, and finally drying at 60 to 100°C for 8 to 16 hours to obtain vinyl mesoporous silica.

3. The method for preparing a halogen-free flame-retardant epoxy resin copper-clad laminate according to claim 2, characterized in that: The raw material components of the vinyl mesoporous silica are as follows: 50 to 80 parts by weight of poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol), 90 to 120 parts by weight of tetraethoxysilane, 80 to 100 parts by weight of vinyl triethoxysilane, 200 to 300 parts by weight of hydrochloric acid, and 3,000 to 4,000 parts by weight of deionized water.

4. The method for preparing a halogen-free flame-retardant epoxy resin copper-clad laminate according to claim 1, characterized in that: The specific process of S2 is: mix vinyl mesoporous silica, vinyl acetate, azobisisobutyronitrile and methanol evenly, stir and react at 50-80°C, when the reactant becomes viscous, add appropriate amount of methanol to dilute, after cooling, dry and crush the product to obtain polyvinyl acetate modified mesoporous silica; mix polyvinyl acetate modified mesoporous silica, sodium hydroxide and methanol evenly, continue stirring at 30-60°C, filter after the reaction is completed, and dry to obtain polyvinyl alcohol modified mesoporous silica.

5. The method for preparing a halogen-free flame-retardant epoxy resin copper-clad laminate according to claim 4, characterized in that: The raw material components of the polyvinyl acetate modified mesoporous silica are as follows: 30-80 parts of vinyl mesoporous silica, 100-300 parts of vinyl acetate, 0.1-1 parts of azobisisobutyronitrile, and 60-90 parts of methanol; the raw material components of the polyvinyl alcohol modified mesoporous silica are as follows: 20-50 parts of polyvinyl acetate modified mesoporous silica, 2-6 parts of sodium hydroxide, and 100-150 parts of methanol.

6. The method for preparing a halogen-free flame-retardant epoxy resin copper-clad laminate according to claim 1, characterized in that: In S3, the preparation process of the composite flame retardant is: the acid source, the gas source and the aldehyde are mixed evenly, the temperature is raised to 40-60°C, stirring is continued, and after reacting for 1-3 hours, polyvinyl alcohol-modified mesoporous silica is added, stirring is continued at 40-60°C, and after reacting for 12-24 hours, the composite flame retardant is obtained.

7. The method for preparing a halogen-free flame-retardant epoxy resin copper-clad laminate according to claim 6, characterized in that: The composite flame retardant comprises the following raw materials in parts by weight: 1 to 3 parts of polyvinyl alcohol-modified mesoporous silica, 3 to 8 parts of an acid source, 1 to 3 parts of a gas source, and 0.1 to 2 parts of an aldehyde; the acid source comprises one of amino-containing thiols and amino-containing benzene sulfonates; the gas source comprises one of melamine and a melamine derivative.

8. The method for preparing a halogen-free flame-retardant epoxy resin copper-clad laminate according to claim 1, characterized in that: The raw material components of the prepreg liquid are as follows: 80-120 parts of bisphenol A epoxy resin, 5-15 parts of curing agent, 2-8 parts of curing accelerator, 40-80 parts of solvent, 20-50 parts of composite flame retardant and 5-20 parts of modified aluminum hydroxide. 9 . The halogen-free flame retardant epoxy resin copper clad laminate prepared according to the method for preparing a halogen-free flame retardant epoxy resin copper clad laminate according to any one of claims 1 to 8 .

Citation Information

Patent Citations

  • Halogen-free resin composition and preparation method thereof, prepreg and preparation method thereof, laminated board and preparation method thereof

    CN110655757A

  • Novel elastomer coating and preparation method thereof

    CN111909608A

  • Flame-retardant low-dielectric LCP-based LDS composite material and preparation method thereof

    CN115772335A

Cited By

  • High-frequency copper-clad plate with high peel strength and preparation method thereof

    CN120287666A